Model of Political Expression of People in the Northeastern Region: Model of Political Expression of People in the Northeastern Region - Phaksupho, Konkhum; Kenaphoom, Sanya; Phosing, Phakdee (RATANABUTH JOURNAL, 2025)
This research aims to 1) study the level of political expression of people in the Northeast, 2) study the factors affecting political expression of people in the Northeast, and 3) create and confirm a model of political expression of people in the Northeast. The mixed research method was divided into 3 phases: Phase 1 was a quantitative research. The sample consisted of 400 people in the Northeast, who were selected by using Taro Yamane’s formula, using the proportional sampling method and simple random sampling. The research instrument was a questionnaire. Data were analyzed using descriptive statistics, mean, percentage, standard deviation, and structural equation analysis (SEM). Phase 2 was a qualitative research. The target group consisted of 20 experts and stakeholders. The research instrument was an interview form. Phase 3 confirmed the model of political expression of people in the Northeast by experts. The research results found that (1) the level of decision-making in voting of people in the Northeast was overall at a high level. (2) Factors affecting political expression of people in the Northeast included politicians’ qualifications, political marketing factors, and political environment factors. It can predict 48.30 percent with statistical significance at the .01 level. The model is consistent with the empirical data. P-Value = 0.207, / = 1.630, GFI = 0.994, CFI = 0.992, RMSEA = 0.04, SRMR = 0.03 (3) The model of political expression of people in the Northeast region consists of the following development guidelines: 1) Development of politicians’ qualities, 2) Development of political marketing, 3) Development of political environment, and (4) The results of the model confirmation are most appropriate and experts have consistent opinions with a median between 4.00-5.00 and an interquartile range of less than 1.5.